ICE manual of structural design buildings - Bull. John W. (ICE manuals, 2012)
Part of the "ICE Manuals" series, "ICE Manual of Structural Design" is the essential reference for all structural engineers involved in the design of buildings and other structures. The manual takes a project oriented approach, covering key issues that design professionals face at the outset of a project such as sustainability, risk management and how to understand the client's needs, before going on to cover the core issues of concept design and the detailed design of structural components. "ICE Manual of Structural Design": approaches the key issues relating to design as they would arise on a typical project; provides an understanding of the key structural design issues at concept design stage; and, gives practical advice on designing structural components to Eurocode specifications. "ICE Manual of Structural Design" is an invaluable resource for all engineers engaged in any aspect of structural design projects.